PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG PENTINGNYA PEMERIKSAAN HBA1C DAN PENGENDALIAN TEKANAN DARAH PADA PASIEN DIABETES MELITUS MELALUI EDUKASI - Sa’adah Siregar; Ika Nur Saputri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diabetes mellitus is a chronic disease that is frequently accompanied by hypertension and may increase the risk of complications if not properly controlled. Limited public understanding regarding the importance of HbA1c testing and blood pressure management has become the basis for implementing this community service activity. This activity aimed to improve community knowledge about the importance of HbA1c examination as an indicator of glycemic control and blood pressure management among patients with diabetes mellitus. The methods included health education, counseling sessions, blood pressure measurements, and consultations on diabetes management based on research findings conducted. The results showed an improvement in participants’ understanding of the importance of regular HbA1c monitoring, blood pressure control, and the implementation of a healthy lifestyle to prevent diabetes-related complications. This activity is expected to enhance public awareness and encourage sustainable diabetes mellitus management